Impact assessment of AICCRA project at MESO level: Experience from Zambia - Manoti, D.; Kikulwe, E.; Kakwasha, K.; Barlis, A. (2025)
The study employed qualitative methods, including key informant interviews of project partners and SMEs, focus group discussions with smallholder farmers, direct field observations, and a comprehensive desk review of project documents to triangulate findings. This assessment sought to (1) evaluate AICCRA’s contribution to enhancing the capacity of next users in generating knowledge products and tools for scaling CIS and CSA; (2) document effective scaling pathways improving CIS/CSA dissemination; and (3) assess alignment with national climate priorities and policies at the meso level in Zambia.